Pteroptyx maipo Ballantyne, a new species of bent-winged firefly (Coleoptera: Lampyridae) from Hong Kong, and its relevance to firefly biology and conservation - Ballantyne, Lesley; Fu, Xin Hua; Shih, Chun-Hat; Cheng, Chui-Yu; Yiu, Vor (Zootaxa, 2011)
Pteroptyx maipo sp. nov. is the first record of the genus Pteroptyx Olivier from mainland China and Hong Kong and represents the most northerly record for this genus. The description includes all life stages: egg, larva, pupa and adult, and covers special structures such as the female bursa plates and male copulatory clamp. Details of habitat, male courtship flash patterns and male-female courtship behaviour are described. This species is the second in the genus Pteroptyx found to use a copulatory clamp, which functions to wedge the mating pair together. A complete clamp however does not appear necessary for successful insemination. Bursa plates hold the spermatophore partially projecting into a spermatophore-digesting gland. Other functions for the plates are investigated and discussed. The deflexed elytral apex appears after eclosion in the adult male. Mechanisms for the loss of ventrite 8 in the male abdomen are explored. A list of the 30 Pteroptyx species recognised here, with habitats, some morphological characteristics and a key to species of the Oriental Pteroptyx are provided.